Edukasi dan Screening Infeksi Plasmodium Penyebab Penyakit Malaria di SMP Negeri 20 Sigi - Nelky Suriawanto; Matius Paundanan (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Malaria remains a significant public health problem in endemic regions, including Central Sulawesi. School-age children are particularly vulnerable due to outdoor activities and limited knowledge of prevention. This community service activity aimed to improve students’ knowledge and conduct malaria screening at SMP Negeri 20 Sigi. The methods included health education through lectures, discussions, and leaflets, as well as laboratory examinations using thick and thin blood smears. The activity was conducted on June 20, 2025, involving 30 students as respondents. The results showed that thin blood smear examinations identified 26 students (86.7%) as positive and 4 students (13.3%) as negative, while thick blood smear examinations revealed 27 students (90%) positive and 3 students (10%) negative. The high number of positive cases indicated that malaria remains a serious health problem among students. Educational activities were effective in enhancing students’ understanding of malaria transmission, symptoms, and prevention. In conclusion, the combination of education and blood smear screening was effective in raising awareness and detecting malaria infections early, thereby supporting malaria prevention and control efforts in endemic areas.